A review of problem solving capabilities in lean process management - A. Perumal, Puvanasvaran; Muhamad, Mohd Razali; Megat Ahmad, Megat Mohamad Hamdan; Tang, Sai Hong; Hamouda, Abdel Magid Salem (Science Publications, 2008)
Human factor plays an important role in ensuring lean process management to be successful and provides good proposition for the success of the organization in the long run. One of the main elements of people is their problem solving capability in identifying and eliminating wastages. The purpose of this paper was to review problem solving capabilities in lean process management; and identifying the important factors and needs for lean process management. Beside that the paper also proposed the conceptual framework of people development system which can help organizations to enhance employees' capability in identifying and eliminating wastages continuously and effectively.